Penerapan Metode SMART untuk Rekomendasi Pencari Kerja Terbaik - Sukamto Sukamto; Yanti Andriyani; Chairia Oktaviani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
PT. PLN (Persero) in serving the community requires quality human resources. The quality of employees in supporting the advancement of a company is very important, so many companies are trying to have quality employees. The way that can be done is by recruiting prospective job seekers in accordance with the criteria desired by the company, it's just that so far many companies have problems in the filing and sorting process because it is done manually, so the results do not match the criteria for the desired job seekers So we need a decision support system with the Simple Multi Attribute Rating Technique method to provide recommendations for the best job seekers with the criteria for Endurance tests, academic tests, psychological tests, laboratory tests and interview tests. The final result of this SPK is that it can provide recommendations for the best job seekers in accordance with the specified criteria.